Maintain oral hygiene for children with special needs - Alifailmazurao, Chindy (BKM Public Health and Community Medicine, 2021)
Challenge 1: the problem of most children is still neglecting to maintain oral hygiene, especially for children with special needs. Most of the reasons they are lazy, too tired, forgetful, and have limited movement in brushing their teeth. Usually, parents and children come to the health service only when the tooth hurts. For that we need people who drive a good and correct tooth brushing action program, especially for those with special needs according to health recommendations Challenge 2: program action that can be practiced today We can study the success of brushing teeth, especially for children with special needs, there are many methods and media that we can learn from various regions to abroad regarding how to maintain oral hygiene, especially children with special needs. Challenge 3: Little things that can help children with special needs in fulfilling their success in cleaning the oral cavity? education for parents and caregivers who are very active in cleaning the teeth of children with special needs by paying attention to the food consumed by children. Because if you eat sweet foods too often, it's easy to make cavities Challenge 4: community groups that can be involved in this activity Community support such as cadres of posyandu, RT, disability community, activists engaged in providing services for children with special needs, teachers in schools, health professionals can be invited to support this creative idea. Challenge 5: how can your innovation be inserted into the existing program? It is better because if the program already exists we can improve the shortcomings of the program so that the program runs better in accordance with our expectations. Challenge 6: related social media The number of programs from the government is still not fully realized because it still requires active silverware from health professionals in addressing dental and oral health problems, especially for children with special needs.